Coming to Terms with John F. Kennedy - Knott, Stephen F. (Book collections on Project MUSE., 2022)
"Stephen F. Knott has spent his life grappling with the legacy of President John F. Kennedy: JFK was the first president Knott remembers; he worked for Ted Kennedy's Senate campaign in 1976; and later he worked at the JFK Library in Boston. Moreover, his scholarly work on the American presidency has wrestled with Kennedy's time in office and whether his presidency was ultimately a positive or negative one for the country as a whole. After initially being a strong Kennedy fan, Knott's views began to sour during his time at the Library, eventually leading him to become a "Reagan Democrat." The Trump presidency led Knott to revisit JFK, leading him once more to reconsider his views. Coming to Terms with John F. Kennedy offers a nuanced assessment of the 35th president, whose legacy people continue to fight over to this day. Knott examines Kennedy through the lens of five critical issues: his interpretation of presidential power, his approach to civil rights, and his foreign policy toward Cuba, the Soviet Union, and Vietnam. Knott also explores JFK's assassination and the evolving interpretations of his presidency, both highly politicized subject matters. What emerges is a president as complex as the author's shifting views about him"--